El papel de la cooperación alemana en las alianzas público-privadas para el desarrollo sostenible en América Latina - Heike Clara Pintor-Pirzkall (Revista Iberoamericana de Estudios de Desarrollo)
Within the framework of South-South cooperation, Germany participates today in new modalities of development cooperation such as triangular cooperation and public-private partnerships (PPP), which have become vital tools for the development of infrastructures in the region, which would not have been viable without the support of the private sector. The German Cooperation Agency (GIZ), the Latin American Energy Organization (OLADE) and the Economic Commission for Latin America (ECLAC) have developed an ambitious program (Proyecto Energía y Desarrollo Sustentable en América Latina), that we will use in this article in order to assess the role of the PPP, the importance of Germany as a main actor in the promotion of sustainable projects and their benefits and impact on integration in the Latin American continent.